(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Religious festivals are celebrations that are held by particular communities that follow a particular religion or set of beliefs. This attempt is to know more about the Cultural significance of religious festivals in Kanyakumari District. It helps to unite people from different cultures and religions in a friendly atmosphere, removing any misunderstanding between them. It is also a great chance to celebrate peace and love and spread it throughout the world. A festival is an extraordinary event celebrated by a community and centering on some characteristic aspect or aspects of that community and its religion or cultures. A festival constitutes typical cases of globalization, as well as the high culture-low culture interrelationship. Next to religion and folklore, a significant origin is agricultural. Food is such a vital resource that many festivals are associated with harvest time. Religious commemoration and thanksgiving for good harvests are blended in events that take place in autumn. Dravidian culture is significant in Tamil Nadu.